Mobilisation of Generation Capacity for the German Electricity Market - Jonas Egerer; Veronika Grimm; Lukas M. Lang; Ulrike Pfefferer; Christian Sölch (Wirtschaftsdienst)
Abstract The energy crisis is forcing Germany and other EU countries to reconsider and, if necessary, adjust energy policy decisions. New perspectives envisage a rapid expansion of renewable energies in the next few years. In the short term, Germany is considering reactivating coal-fired power plants from the reserve and revising decisions to decommission coal-fired and nuclear power plants in the coming years. This brief study analyses the price effects for the years 2024 and 2027 to shed light on both the short-term challenges and the medium-term prospects.